Digestive Tract and the Muscular Pharynx/Esophagus in Wild Leptocephalus Larvae of European Eel (Anguilla anguilla) - Knutsen, Helene Rønquist; Sørensen, Sune Riis; Munk, Peter; Bardal, Tora; Kjørsvik, Elin (Frontiers in Marine Science, 2021)
Several aspects of the biology of European eel (Anguilla anguilla) larvae is still unknown; particularly, information about their functional development and feeding is sparse. In the present study, we histologically characterize the digestive system of wild caught specimens of European eel leptocephalus larvae. The aim was to provide more understanding about how food may be ingested and mechanically processed in the leptocephalus larvae, and to discuss this in context of it’s hypothesized feeding strategy. Larvae were caught in the Sargasso Sea during the “Danish Eel Expedition 2014” with the Danish research vessel Dana. The larval sizes ranged from 7.0-23.3 mm standard length (SL) at catch. We found that the mouth/pharynx, and especially the anterior esophagus was surrounded by a multi-layered striated muscle tissue, and that the epithelium in the mouth/pharynx had a rough filamentous surface, followed by epithelial columnar cells with multiple cilia in the anterior esophagus. This suggests an expandable pharynx/esophagus, well-suited for transportation of ingested food and likely with a food-crushing or grinding function. The digestive tract of the larvae consisted of a straight esophagus and intestine ventrally aligned within the larval body and its length was linearly correlated to the larval length (SL). The length of the intestinal part constituted up to 63% of the total length of the digestive tract. The intestinal epithelium had a typical absorptive epithelium structure, with a brush border and a well-developed villi structure. Some cilia were observed in the intestine, but any surrounding muscularis was not observed. The liver was observed along the posterior part of the esophagus, and pancreatic tissue was located anterior to the intestine. Our findings support the hypothesis that the eel leptocephalus may ingest easily digestible gelatinous plankton and/or marine snow aggregates. The muscular esophagus and the ciliated epithelium appear sufficient to ensure nutrient transport and absorption and transport of the ingested food through the digestive tract.